2020
DOI: 10.3389/fnhum.2020.00311
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Factors in Musicians’ Performance Tempo

Abstract: Musicians display individual differences in their spontaneous performance rates (tempo) for simple melodies, but the factors responsible are unknown. Previous research suggests that musical tempo modulates listeners' cardiovascular activity. We report an investigation of musicians' melody performances measured over a 12-h day and subsequent changes in the musicians' physiological activity. Skilled pianists completed four testing sessions in a single day as cardiac activity was recorded during an initial 5 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 71 publications
(116 reference statements)
1
18
1
Order By: Relevance
“…This effect did not interact with the other factors. These findings are in line with the chronobiological effects on the SMT and related tasks reported in previous studies (Hammerschmidt et al, 2021 ; Moussay et al, 2002 ; Tamm et al, 2009 ; Wright & Palmer, 2020 ), providing further support that the SMT may directly be influenced by the circadian rhythm of the biological clock, because fluctuations of the SMT over the day depend systematically on the combination of time of the day and participants’ 24-h sleep and activity cycle (i.e., chronotype).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This effect did not interact with the other factors. These findings are in line with the chronobiological effects on the SMT and related tasks reported in previous studies (Hammerschmidt et al, 2021 ; Moussay et al, 2002 ; Tamm et al, 2009 ; Wright & Palmer, 2020 ), providing further support that the SMT may directly be influenced by the circadian rhythm of the biological clock, because fluctuations of the SMT over the day depend systematically on the combination of time of the day and participants’ 24-h sleep and activity cycle (i.e., chronotype).…”
Section: Discussionsupporting
confidence: 91%
“…Results show that the slower the SMT cluster, the earlier was the mean hour of test participation, thus further supporting a direct influence of the biological clock on the SMT pace. Furthermore, a recent study found that musicians’ spontaneous production rate (i.e., tempo) of musical melodies varies as a function of the time of the day, as melody production was slower in the morning (9 am) compared to later times (1 pm, 5 pm, 9 pm; Wright & Palmer, 2020 ). Another study on the cognitive output close to sleep phases investigated the tapping speed of smartphone usage for about three weeks (Huber & Ghosh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that this third framework is not a null hypothesis, which would be the prediction that SPRs are inherently variable and do not lead to consistent rates even within a domain. This null hypothesis is unlikely for music performance, given high consistency of SPRs found in previous work (Zamm et al, 2016;Wright and Palmer, 2020), but it is possible in speech given current debates about whether regular rhythmic organization can account for speech timing.…”
mentioning
confidence: 89%
“…This finding has been replicated in both music performance and tapping tasks, with musicians and non-musicians ( Scheurich et al, 2018 ). Third, the spontaneous rates are consistent within individuals, across their limb movements and melodies ( Zamm et al, 2016 ), across time of day ( Zamm et al, 2019 ; Wright and Palmer, 2020 ). Moreover, recent computational work ( Roman et al, 2020 ) indicates that the relationship between musical partners’ spontaneous frequencies and interpersonal synchrony can be accurately predicted from a model of biological oscillator entrainment, providing further credence to an oscillator framework of musical synchrony.…”
Section: Introductionmentioning
confidence: 94%